2015
DOI: 10.5539/mas.v9n11p119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen on the Corrosion Behavior of Austenitic Stainless Steel in Chloride Solutions

Abstract: The effect of partial replacement of nickel with nitrogen on the corrosion resistance of newly designed austenitic stainless steel samples without and with heat treated was investigated in 3.5wt% and 5wt% NaCl solution using open-circuit, potentiodynamic, cyclic anodic polarization and electrochemical impedance spectroscopy techniques. The results showed that, passivation in sample 1 where the highest addition of nickel and low addition of nitrogen is different from that for sample 4 where the nitrogen is grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The appropriate HTSN parameters can be obtained from calculated isopleths using CALPHAD databases such as ThermoCalc. Here, the phase stability as a function of temperature and nitrogen content is highly relevant [25][26][27][28]. As an illustration, an isopleth for 316L containing an isobar indicating a nitrogen pressure of 300 mbar is given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate HTSN parameters can be obtained from calculated isopleths using CALPHAD databases such as ThermoCalc. Here, the phase stability as a function of temperature and nitrogen content is highly relevant [25][26][27][28]. As an illustration, an isopleth for 316L containing an isobar indicating a nitrogen pressure of 300 mbar is given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this incorporation could be the primary mechanism, which is latter accompanied in different environments by the secondary mechanism of formation of NH 4 + ions. This results in electro-potential discharge [37] of the newly formed "ghost layer" (passive layer) and reduced degradation of the material. The next alloying element analyzed was cobalt (ion forms of Co − and CoO − ), Figures 3d, 4d and 5b-g.…”
Section: Tof-sims Surface Analysesmentioning
confidence: 99%
“…normalN may repel the migration of chloride ions toward the metal surface, mitigating the surficial dissolution. [ 69–71 ] Jayaraj et al [ 70 ] suggested that the negatively charged effect of N, like normalN existing in a passive film, decreased the corrosion reaction and corrosion current. Moreover, the anion could repel the negative SO42 and normalF ions, increasing the corrosion resistance and decreasing the anodic dissolution.…”
Section: The Functional Role Of the Alloying Elementsmentioning
confidence: 99%